Challenges and Solutions in Student Teachers’ Microteaching for English Language Teaching: Tantangan dan Solusi dalam Pengajaran Mikro Mahasiswa Calon Guru untuk Pengajaran Bahasa Inggris - Yundayani, Audi; Alghadari, Fiki (Pedagogia : Jurnal Pendidikan, 2024)
Microteaching experience is a compulsory subject as a practical training technique that provides prospective teachers with many opportunities to design their effective teaching techniques before they are involved in real classroom experiences as English teachers. However, the challenges and solutions in conducting microteaching in student teachers in English language teaching (ELT) remain under-researched. Therefore, this study addressed this issue, notably in Indonesian English as a foreign language. Three student teachers from an English study program of a private educational higher institution were recruited as the participants. The data were collected through semi- structured interviews and analysed with Thematic Analysis (TA). The research result identified themes related to the obstacles English student teachers face in teacher training and education programs when executing the microteaching process and solution. It covers their lack of conceptual knowledge of instructional design, their incapability in classroom management, their lack of understanding of the character of students, their incapability to perceive the role of reflective teaching and their lack of self-confidence. Developing a microteaching endeavour that facilitates practical teaching experiences and enables English teacher candidates to hone their teaching abilities by improving various teaching skills is advisable.